The Influence Of Perceived Enjoyment, Electronic Word Of Mouth, And Social Influence On Robux Purchase Intention With Attitude As A Mediating Variable On Roblox Players In Indonesia - Muhammad Ari Nugraha; Yulyanti Fahruna; Ahmadi Ahmadi; Wenny Pebrianti; Harry Setiawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Roblox has evolved into a digital platform that combines gaming, social interaction, and a virtual economy centered on the in-game currency, Robux. In this environment, players are frequently exposed to community trends, peer influence, and time-limited virtual items that may encourage virtual purchasing behavior. Despite many users being teenagers or young adults with limited income sources, Robux purchases remain common, suggesting that psychological and social factors may strongly influence purchasing decisions. Therefore, this study aims to examine the influence of perceived enjoyment, electronic word of mouth (eWOM), and social influence on Robux purchase intention, with attitude acting as a mediating variable among Roblox players in Indonesia. A quantitative research approach was employed, utilizing an online questionnaire distributed through social media and Roblox communities. Data from 172 respondents were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that perceived enjoyment, eWOM, and social influence significantly affect attitude. Attitude exerts a strong positive effect on purchase intention and mediates the relationship between the independent variables and purchase intention. Among the variables examined, social influence is the most dominant factor shaping attitudes toward Robux purchases. These results underscore the significance of social interaction, community influence, and perceived enjoyment in shaping virtual purchase behavior within online gaming ecosystems.